Results from a clinical yoga program for veterans: yoga via telehealth provides comparable satisfaction and health improvements to in-person yoga - R. Jay Schulz-Heik; Hilary Meyer; Louise Mahoney; Michael V. Stanton; Rachael H. Cho; Danae P. Moore-Downing; Timothy J. Avery; Laura C. Lazzeroni; Joanne M. Varni; Linda Martin Collery; Peter J. Bayley (BMC, 2017)
Abstract Background Yoga is increasingly popular, though little data regarding its implementation in healthcare settings is available. Similarly, telehealth is being utilized more frequently to increase access to healthcare; however we know of no research on the acceptability or effectiveness of yoga delivered through telehealth. Therefore, we evaluated the feasibility, acceptability, and patient-reported effectiveness of a clinical yoga program at a Veterans Affairs Medical Center and assessed whether these outcomes differed between those participating in-person and those participating via telehealth. Methods Veterans who attended a yoga class at the VA Palo Alto Health Care System were invited to complete an anonymous program evaluation survey. Results 64 Veterans completed the survey. Participants reported high satisfaction with the classes and the instructors. More than 80% of participants who endorsed a problem with pain, energy level, depression, or anxiety reported improvement in these symptoms. Those who participated via telehealth did not differ from those who participated in-person in any measure of satisfaction, overall improvement (p = .40), or improvement in any of 16 specific health problems. Conclusions Delivering yoga to a wide range of patients within a healthcare setting appears to be feasible and acceptable, both when delivered in-person and via telehealth. Patients in this clinical yoga program reported high levels of satisfaction and improvement in multiple problem areas. This preliminary evidence for the effectiveness of a clinical yoga program complements prior evidence for the efficacy of yoga and supports the use of yoga in healthcare settings.